Perancangan Lengan Robot Berbasis Arduino dengan 4 Servo Motor - Andira Andira; Awaluddin Harahap; Wandani Putri Siregar; Eka Dodi Suryanto; Dian Putra Saragih (JURNAL ILMIAH NUSANTARA, 2026)
The rapid development of robotics technology drives the need for efficient automation systems, particularly in the industrial and educational sectors. One widely developed implementation is the robotic arm that can mimic human movements to manipulate objects with precision. This research aims to design and build a robotic arm prototype based on an Arduino microcontroller with four servo motors as the main actuators. The methods used include stages of information gathering, system requirements analysis, mechanical and electronic design, hardware construction, programming using the Arduino IDE, and system testing. The research results show that a robotic arm system with four degrees of freedom (4 DOF) is capable of performing basic movements such as picking up, lifting, and moving objects quite well. The integration between mechanical systems, electronics, and software works optimally, with the microcontroller able to controlling the movement of the servo in a coordinated manner. The robot can also be operated in manual mode using a joystick or in automatic mode based on predetermined parameters. Tests show that the robot is able to lift loads up to 350 grams optimally, but experiences limitations with larger loads. The implication of this research is that the designed system can be used as an effective learning medium for understanding basic robotics concepts, particularly related to actuators, control systems, and system integration.